Histological analysis and gene expression profile following augmentation of the anterior maxilla using rhBMP-2/ACS versus autogenous bone graft - de Freitas, Rubens Moreno; Susin, Cristiano; Tamashiro, Wirla Maria da Silva Cunha; Chaves de Souza, João Antonio; Marcantonio, Claudio [UNESP]; Wikesjö, Ulf ME; Pereira, Luís Antônio Violin Dias; Marcantonio, Elcio [UNESP] (Wiley, 2016)
Aim: The objective of this report was to present histological characteristics and gene expression profile of newly formed bone following horizontal augmentation of the atrophic anterior maxilla using recombinant human bone morphogenetic protein-2 in an absorbable collagen sponge carrier (rhBMP-2/ACS) versus an autogenous bone graft (ABG). Methods: Bone core biopsies from 24 subjects participating in a randomized clinical trial were obtained at dental implant placement, 6 months following alveolar ridge augmentation using rhBMP-2/ACS (rhBMP-2 at 1.5 mg/ml; total dose 4.2 mg) or a particulate ABG harvested from the mandibular retro-molar region. A titanium mesh was used to provide wound stability and space for bone formation. Analysis included histological/histometric observations and gene expression profile of the newly formed bone. Results: rhBMP-2/ACS yielded bone marrow rich in capillaries, undifferentiated cells and bone lining cells compared with the ABG (p = 0.002). Whereas no significant differences were observed in total bone fraction (p = 0.53), non-vital bone particles trapped in lamellar vital bone were observed in the ABG group (p < 0.001). Real-time PCR showed greater BMP-2 and RUNX2 expression for rhBMP-2/ACS over the ABG (p = 0.001 and 0.0021, respectively), while the ABG exhibited greater expression of RANKL:OPG, BSP and OPN over rhBMP-2/ACS (p = 0.01, 0.005 and 0.0009, respectively). Conclusions: Our observations suggest that formative biological processes explain bone formation following implantation of rhBMP-2/ACS, whereas remodelling, resorptive/formative processes, characterizes sites receiving ABGs.
Keywords: alveolar ridge augmentation; autogenous bone graft; randomized controlled trial; recombinant human bone morphogenetic protein; rhBMP-2